Study of sociodemographic profile of juvenile boys admitted in an observation home - Bhoge, Nitin D.; Panse, Smita N.; Pawar, Alka V.; Raparti, Girish T.; Ramanand, Sunita J.; Ramanand, Jaiprakash B. (International Journal of Advances in Medicine, 2017)
Background: World Health Report estimated that 20% of children and adolescent suffer from a disabling mental illness worldwide. Incidences of vagrancy, delinquency and crime have been growing among steadily increasing juvenile population in the last few years. Various studies have revealed the presence of difficult family environment, lower socio-economic status, and low parental education associated with the psychiatric morbidity in children. Given the growth of juvenile delinquent population, epidemiologic data of this high risk group is becoming increasingly important. Therefore this study was undertaken to study the sociodemographic profile of male juvenile admitted in an observation home. Methods: This cross sectional study was conducted in an Observation Home for Boys. The study sample consists of 50 boys aged between 6-16 years. Out of 50, 20 juveniles under conflict of law and 30 under care and protection were included. Results: All the juveniles in this study were belonging to the lower socioeconomic status. Delinquency was significantly more common in older age group (12-16 years) than younger age group (6-11 years). The maternal education and school dropout rate had significant correlation with delinquency in our study, found to be more common in juveniles under conflict of law than those under care and protection. Conclusions: Establishment of multidisciplinary mental health services at each juvenile center of India, for complete rehabilitation of the juveniles admitted there, under social justice system is immediately required.